Long-term care staffs' experience in facilitating the use of videoconferencing by cognitively impaired long-term care residents during the COVID-19 pandemic: a mixed-methods study - Marie-Soleil Hardy; Chaimaa Fanaki; Camille Savoie; Machelle Wilchesky; Marie-Pierre Gagnon; Maude Laberge; Vincent Couture; André Côté; Clémence Dallaire; Philippe Voyer; Maria Cecilia Gallani; Bernadette Dallaire; et al. (BMC, 2024)
Abstract Background During the COVID-19 pandemic, numerous long-term care (LTC) homes faced restrictions that prevented face-to-face visits. To address this challenge and maintain family connections, many LTC homes facilitated the use of electronic tablets to connect residents with their family caregivers. Our study sought to explore the acceptability of this practice among staff members and managers, focusing on their experiences with facilitating videoconferencing. Methods A convergent mixed method research was performed. Qualitative and quantitative data collection through semi-structured interviews to assess the acceptability of videoconferencing in long-term care homes and to explore the characteristics of these settings. Quantitative data on the acceptability of the intervention were collected using a questionnaire developed as part of the project. The study included a convenience sample of 17 staff members and four managers. Results Managers described LTC homes' characteristics, and the way videoconferencing was implemented within their institutions. Affective attitude, burden, ethicality, opportunity costs, perceived effectiveness, and self-efficacy are reported as per the constructs of the Theoretical Framework of Acceptability. The results suggest a favorable acceptability and a positive attitude of managers and staff members toward the use of videoconferencing in long-term care to preserve and promote contact between residents and their family caregivers. However, participants reported some challenges related to the burden and the costs regarding the invested time and staff shortage. Conclusions LTC home staff reported a clear understanding of the acceptability and challenges regarding the facilitation of videoconferencing by residents to preserve their contact with family caregivers.